[tex]y = - \frac{2}{3} x + \frac{20}{3} [/tex]
Step-by-step explanation:
y=mx+c
label your points
(-2;8). pnt2
(4;4). pnt1
[tex]m = \frac{y2 - y1}{x2 - x1} [/tex]
[tex]m = \frac{8 - 4}{ - 2 - 4} [/tex]
[tex]m = \frac{ 4}{ - 6} [/tex]
[tex]m = - \frac{2}{3} [/tex]
substitute gradient and 1 point into equation to get c
[tex]8 = ( - \frac{2}{3} )( - 2) + c[/tex]
[tex]8 = \frac{4}{3} + c[/tex]
[tex]c = 8 - \frac{4}{3} [/tex]
[tex]c = \frac{20}{3} [/tex]
Therefore the equation is
[tex]y = - \frac{2}{3} x + \frac{20}{3} [/tex]